The value of fine needle aspiration cytology in the clinical management of rare salivary gland tumors - Tibor Mezei (Journal of Applied Oral Science, 2018)
Abstract Salivary gland tumors are relatively rare neoplasms, mostly located in the parotid gland, and few are malignant. Preoperative evaluation of salivary gland tumors includes fine needle aspiration cytology (FNAC). Objective The purpose of this study was to determine the importance of FNAC in the evaluation of rare salivary gland neoplasms. Material and Methods Four cases of rare salivary gland tumors were included, which were preoperatively assessed by clinical investigation, computed tomography, and FNAC. Results The presented cases include myoepithelial carcinoma, oncocytic carcinoma, undifferentiated lymphoepithelial carcinoma, and marginal zone lymphoma. Conclusion FNAC is a reliable diagnostic tool for common salivary gland neoplasms; however, rare tumors often represent diagnostic challenges. Clinical relevance In such rare tumors, the role of aspiration cytology may be limited to establishing the dignity of the lesion (benign/malignant). This knowledge enables the surgeon to choose the most appropriate therapeutic procedure. A definitive diagnosis of rare tumors (either epithelial or nonepithelial) is obtained by histological examination; cytology is limited in this regard due to overlapping features.